A Recurrent Nonsense Mutation in NECTIN4 Underlying Ectodermal Dysplasia-Syndactyly Syndrome with a Novel Phenotype in a Consanguineous Kashmiri Family - Ghazanfar Ali; Sadia Sadia; Syeda Ain-ul- Batool; Zahid Azeem; Naheed Bashir Awan; Syed Akif Raza Kazmi; Zia- Ur- Rehman; Zeeshan Anjum; Fazal- Ur- Rehman; Abdul Wali; Kafaitullah Khan; Nasib Zaman; et al. (Genetics Research)
EDSS1, a syndrome characterized by ectodermal dysplasia-syndactyly, is inherited in an autosomal recessive manner due to mutations in the NECTIN4/PVRL4 gene. Clinical manifestations of the syndrome include defective nail plate, sparse to absent scalp and body hair, spaced teeth with enamel hypoplasia, and bilateral cutaneous syndactyly in the fingers and toes. Here, we report a consanguineous family of Kashmiri origin presenting features of EDSS1. Using whole exome sequencing, we found a recurrent nonsense mutation (NM_030916: c.181C > T, p.(Gln61 ∗)) in the NECTIN4 gene. The variant segregated perfectly with the disorder within the family. The candidate variant was absent in 50 in-house exomes pertaining to other disorders from the same population. In addition to the previously reported clinical phenotype, an upper lip cleft was found in one of the affected members as a novel phenotype that is not reported by previous studies in EDSS1 patients. Therefore, the study presented here, which was conducted on the Kashmiri population, is the first to document a NECTIN4 mutation associated with the upper lip cleft as a novel phenotype. This finding broadens the molecular and phenotypic spectrum of EDSS1.